Efeito antifúngico do mesocarpo de babaçu (Attalea speciosa Mart.) na infecção letal por Candida sp. - BARBOSA, Nicolle Teixeira (2024)
Species of the genus Candida are familiar in human microbiota, but they are also considered opportunistic fungi since they can cause infections at different sites and can be lethal. Thus, there is a constant search for compounds with antifungal action, and, in this context, babassu emerged as a plant species with high biotechnological potential since previous studies have demonstrated the anti-Candida activity in vitro. Therefore, this study evaluated the anti- Candida sp. properties of the babassu mesocarp (BAE) ethanolic extract in vitro and in vivo. The chemical composition of BAE was determined by liquid chromatography, in which the chromatograph was coupled to a mass spectrometer and the acquisition range was m/z 100– 1500, with two or more events. The anti-Candida activity in vitro determined the anti-virulence activity on adhesion and biofilm formation. The anti-Candida effect was also determined in vitro using murine macrophages. Tenebrio molitor larvae were used to assess the toxicity of BAE and its anti-lethal effect after infection with C. albicans and C. parapsilosis. The anti- infective effect of BAE was determined in vivo using Swiss mice infected with C. parapsilosis. The chemical evaluation of BAE identified the presence of seven compounds including: vicenin-2, isoschaftoside, schaftoside, orientin, apigenin-6-C-glucoside-8-C-arabinoside, apigenin-7-rutinoside and isochlorogenic acid. BAE showed low toxicity in vitro and in vivo. The in vitro results showed that BAE inhibited both adhesion and biofilm of standard and clinical samples of C. albicans and C. parapsilosis. The in vivo results showed that BAE at concentrations of 2× and 4× MIC increased the survival of T. molitor larvae infected with C. albicans or C. parapsilosis and reduced infection in murine macrophage cultures. BAE also reduced the systemic infection of mice infected with Candida parapsilosis, in which the dose corresponding to 2x CIM (33.4 mg/mL) resulted in a reduction of CFUs in the blood, liver and kidneys and the dose corresponding to the CIM value (16.7 mg/mL) was effective in reducing the number of CFUs in the liver and kidneys. In addition, the treatment of mice with BAE had different effects when evaluating the activation of neutrophils and T lymphocytes and always reduced the activation of macrophages. The blood biochemistry data of infected mice treated with the extract showed that treatment with BAE at a concentration of 2×CIM increased the concentration of glucose and cholesterol, decreased the concentration of triglycerides compared to the positive control, but did not differ from the other groups in the concentrations of urea and creatinine. We conclude that BAE has antifungal action in the lethal infection caused by Candida sp., due to its ability to inhibit both adhesion and biofilm, resulting in reduced infection of macrophages and mice, which may be related to the synergistic action of the compounds found in our extract.